2013
DOI: 10.5045/br.2013.48.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Acute pyelonephritis with anaplastic thyroid carcinoma producing granulocyte colony-stimulating factor

Abstract: Paraneoplastic leukocytosis was defined as elevated white blood cell (WBC) levels caused by cytokines, likely produced by the tumor itself, without evidence of infection or myeloproliferative disease. We report a case of anaplastic thyroid carcinoma with leukocytosis caused by elevated production of granulocyte colony-stimulating factor (G-CSF) by the carcinoma. Initially, acute pyelonephritis (APN) was diagnosed and treatment for APN was ongoing, but the WBC count steadily increased to 68.8×109/L. She was dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Most G-CSFeproducing tumors are poorly differentiated and are likely to develop distant metastases. 8,11,12,[14][15][16][17][19][20][21][22] G-CSF stimulated the growth of a nonhematopoietic malignant cell line in vivo, 28 and G-CSF was also considered to be a major autocrine growth factor in rapid tumor proliferation and metastasis. 29 It has also been suggested that G-CSF has a priming effect on platelet aggregation and thrombin generation and subsequently induces a hypercoagulable state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most G-CSFeproducing tumors are poorly differentiated and are likely to develop distant metastases. 8,11,12,[14][15][16][17][19][20][21][22] G-CSF stimulated the growth of a nonhematopoietic malignant cell line in vivo, 28 and G-CSF was also considered to be a major autocrine growth factor in rapid tumor proliferation and metastasis. 29 It has also been suggested that G-CSF has a priming effect on platelet aggregation and thrombin generation and subsequently induces a hypercoagulable state.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, G-CSF can be used to mobilize hematopoietic stem cells from healthy donors to harvest stem cells for transplantation. 7 Several G-CSFeproducing malignant tumors have been reported in the lung, [8][9][10][11] urinary bladder, 12,13 digestive organs, [14][15][16][17][18][19] and thyroid gland, [20][21][22] but not in the breast. We present a rare case of a G-CSFeproducing spindle cell carcinoma of the left breast.…”
Section: Introductionmentioning
confidence: 99%
“…In the following years, increased levels of other cytokines, such as IL-6, IL-1, G-CSF, and macrophage-CSF (M-CSF), were also associated with ATC. In the literature, few cases have been published over the years that associate leukocytosis and cytokine production with ATC (Table 1) [9][10][11][12][20][21][22][23][24][25][26][27][28][29], even though, as previously noted, some other studies relate leukocytosis with poor prognosis in patients with ATC. Most of these reports evaluated CSFs, and in very few cases, IL-6 was measured and was found either elevated or within the normal range [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Paraneoplastic manifestations have been reported in anaplastic thyroid carcinoma. The manifestations comprise ectopic secretion of human chorionic gonadotrophin (Gu et al 2018), fibroblastic growth factor 23 (giving rise to osteomalacia) (Abate et al 2016), granulocyte colonystimulating factor (give rise to leucocytosis) (Kang et al 2013), parathyroid hormone-related protein (give rise to hypercalcemia) (Iwai et al 2004) as well as hypertrophic osteoarthropathy likely to be the effect of secretion of platelet derived growth factor or vascular endothelial growth factor (Vico et al 1992). Similar to anaplastic thyroid carcinoma, paraneoplastic manifestations could occur in patients with primary squamous cell carcinoma of thyroid.…”
Section: Clinical Featuresmentioning
confidence: 99%